[OP.5C.09] OMEGA-6 FATTY ACIDS IN ERYTHROCYTE MEMBRANE ARE INVERSELY ASSOCIATED WITH SEVERAL FEATURES OF THE METABOLIC SYNDROME IN A GROUP OF OBESE CHILDREN. (September 2017) - Bonafini, S.; Tagetti, A.; Mantovani, A.; Donato, A.; Dalbeni, A.; Maffeis, C.; Antoniazzi, F.; Minuz, P.; Fava, C.
Abstract : Objective: Overweight and obesity lead to the clustering of cardiovascular (CV) risk factors and the metabolic syndrome (MetS) not only in adults but also in children and are often accompanied by non-alcoholic fatty liver disease. Quality of dietary fat, beyond the quantity, can influence CV risk profile and in particular omega-3 fatty acids (FA) have been proposed as beneficial. Design and method: The aim of this observational study was to evaluate the associations of individual CV risk factors, characterizing the MetS, with erythrocyte membrane FA (by gas-chromatography), markers of average intake, in a group of obese children. Results: We enrolled 70 children (BMI = 29.4 ± 4.4 Kg/m 2 ; percentile of BMI = 98.0 ± 1.7), aged 5–17 years. Mean content of Omega-3 FA was low (Omega-3 Index = 4.7 ± 0.8%). Omega-3 FA were not associated with MetS characteristics, whereas omega-6 FA, in particular arachidonic acid (AA), were inversely associated with several features of the MetS: AA resulted inversely correlated with waist circumference (rS = −0.352), waist/hip ratio (rS = −0.311), Waist/height ratio (rS = −0.248), triglycerides (rS = −0.366), fasting insulin (rS = −0.337), 24-hour-SBP (rS = −0.313), daytime-SBP (rS = −0.267), nighttime-SBP (rS = −0, 245) and nighttime DBP (rS = −0.344). On the opposite, total amount of saturated FA (SFA) and specifically, palmitic acid, correlated positively with waist circumference (rS = 0.254), waist/hip ratio (rS = 0.247), total cholesterol (rS = 0.258), triglycerides (rS = 0.373) and fasting insulin (rS = 0.287). Thirty-five children (50%) had hepatic steatosis detected by ultrasounds. Fatty Liver Index (FLI), a predictive score of steatosis based on GGT, triglycerides and anthropometric indexes, was directly correlated to SFA (rS = 0.479), palmitic acid (rS = 0.515) and inversely to omega-6 FA (rS = −0.435) and AA (rS = −0.472). AA was inversely correlated with ALT (rS = −0.331) and palmitic acid directly with GGT (rS = 0.339). Conclusions: Omega-6 FA, and especially AA, may be protective toward CV risk factors featuring the MetS and also to indexes of hepatic steatosis in obese children, whereas SFA seems to exert opposite effects.